Hybrid Energy System for a Rural Area - Goyal, Shweta; Mishra, Sachin; Bhatia, Anamika; Jarodia, Puspender Singh (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*71.90px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910059);" role="presentation">Nowadays, renewable energy has received significant research <span dir="ltr" style="left: calc(var(--scale-factor)*329.23px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919465);" role="presentation">attention to reducing greenhouse effects as well <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99927);" role="presentation">as the cost of utilization of electrical po<span dir="ltr" style="left: calc(var(--scale-factor)*242.81px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00947);" role="presentation">wer. A hybrid power station, i.<span dir="ltr" style="left: calc(var(--scale-factor)*374.35px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959903);" role="presentation">e., a combination of renewable and <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91908);" role="presentation">convention power <span dir="ltr" style="left: calc(var(--scale-factor)*146.54px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909126);" role="presentation">station <span dir="ltr" style="left: calc(var(--scale-factor)*175.85px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915394);" role="presentation">could be a good substitute of a conventional plant to reduce global warmi<span dir="ltr" style="left: calc(var(--scale-factor)*470.74px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925946);" role="presentation">ng effects. In <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920704);" role="presentation">anywhere a remote situated area or boondocks may be recherché as a case study in a procedure to inquire the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967338);" role="presentation">accomplishment to apply a hybrid power system and allow to the rural areas. <span dir="ltr" style="left: calc(var(--scale-factor)*403.27px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951821);" role="presentation">The proposed Hybrid energy <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95335);" role="presentation">system is simulated in HOMER s<span dir="ltr" style="left: calc(var(--scale-factor)*210.41px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947979);" role="presentation">oftware. In HOMER software simulation has accomplishment and details of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896521);" role="presentation">concern study are also described in this paper.